Fabrication of polymer/microwave‐reduced graphite oxide nanocomposites by ball‐milling assisted wet compounding. Issue 4 (13th March 2013) - Long, Jiang; Chen, Guohua
Abstract Microwave‐induced reduction of graphite oxide (GO) is a promising method for rapid and scalable production of graphene. However, homogeneous incorporation of thus prepared graphene into polymer matrix is still a hard task. In this article, we present a ball‐milling assisted wet compounding method for the fabrications of microwave‐reduced GO (MRGO)/polymer composites. MRGO powders were added into a solution of polystyrene (PS) and then mechanically exfoliated in a stirring mill. Scanning electron microscopy and transmission electron microscopy investigations show that the graphene sheets have been homogeneously dispersed in the PS matrix. The composites show pronouncedly improved properties. The thermal degradation temperature of composites increased by 34°C with the addition of 5wt% MRGO in PS. Up to 76% improvement of storage modulus (at 30°C) is achieved by compounding with 10wt% MRGO.POLYM. COMPOS., 2013. © 2013 Society of Plastics Engineers